Calculation of Deflection of Vertical and Gravity Anomalies Over the South China Sea Derived from ICESat-2 Data - Che, Defu; Li, Hang; Zhang, Shengjun; Ma, Baodong (Frontiers in Earth Science, 2021)
The Ice, Cloud, and land Elevation Satellite-2 (ICESat-2) satellite uses a synchronized multi-beam photon-counting method to collect data from three pairs of synchronous ground tracks. The sampling rate along the ground tracks is designed to be ∼0.7 m, much smaller than that used in conventional radar altimeters. Hence, it is reasonable to expect an improvement in marine gravity recovery over coastal zones using ICESat-2 data. ICESat-2 provides valid sea surface height (SSH) measurements and a standard data product (ATL12) over ocean areas. This led us to consider the possibility of investigating its ability to calculate the deflection of vertical (DOV) and marine gravity anomalies. We processed ATL12 data about 22 months over the South China Sea (0°–23°N, 103°–120°E) and verified the ability of ICESat-2 SSH measurements to be used in calculating directional components of DOV. The results show that the ICESat-2 SSH data have a similar centimeter-magnitude accuracy level as data from the Jason-2 satellite. Furthermore, the accuracy of cross-track deflection of vertical (CTDOV) calculations between non-identical side beams is lower. For along-track points, the difference in accuracy between the solution of the prime component and the meridional component is significantly reduced, the prime component accuracy is significantly better than the directional components of the gridded deflection of vertical (GDOV), although the enhancement is weak for the meridional component. We also implemented the inversion of the ICESat-2 single mission based on the inverse Vening Meinesz formula, and verified the capability of ICESat-2 gravity field detection using shipborne gravity measurements and XGM2019 gravity field model, and found that the accuracy is 1.35 mGal and 2.47 mGal, respectively. ICESat-2 deserves the attention of the altimetry community, and its advantages are expected to make it an alternative data source for multi-mission fusion inversion of the ocean gravity field in the future.